2009
DOI: 10.1001/archfaci.2009.5
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Safety and Efficacy of a New Botulinum Toxin Type A in Treating Glabellar Lines

Abstract: Objective: To evaluate the long-term safety of repeated administrations of a new botulinum toxin type A (Reloxin; Medicis Pharmaceutical Corp, Scottsdale, Arizona) in the treatment of moderate to severe glabellar lines.Methods: Open-label assessment of 1200 patients receiving as many as 5 treatments of Reloxin over a 13month period. The product was diluted in 2.5-mL sterile physiologic saline solution, 0.9%, without preservative to a concentration of 50 U of Reloxin per 0.25 mL of solution. Investigators injec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
66
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 47 publications
(73 citation statements)
references
References 8 publications
7
66
0
Order By: Relevance
“…To the best of our knowledge, this is the first report that demonstrates the effect of different types and dilutions of BoNT‐A toxin on fibroblast contraction. In previous comparisons of ONA to ABO, statistically significant improvements were observed for forehead lines, glabellar frown lines, and crow's feet compared with placebo groups, and a recent comparison of intradermal versus intramuscular BoNT‐A by Sapra et al showed significantly improved skin texture concomitant with a mild midfacial lift. We propose that one potential cellular mechanism underlying this positive outcome is the fibroblast contraction observed here.…”
Section: Discussionmentioning
confidence: 93%
“…To the best of our knowledge, this is the first report that demonstrates the effect of different types and dilutions of BoNT‐A toxin on fibroblast contraction. In previous comparisons of ONA to ABO, statistically significant improvements were observed for forehead lines, glabellar frown lines, and crow's feet compared with placebo groups, and a recent comparison of intradermal versus intramuscular BoNT‐A by Sapra et al showed significantly improved skin texture concomitant with a mild midfacial lift. We propose that one potential cellular mechanism underlying this positive outcome is the fibroblast contraction observed here.…”
Section: Discussionmentioning
confidence: 93%
“…Among the patients who reported effect onset with incoBTX-A treatment, the median result was 8.5 days, longer than the median onset of effect with aboBTX-A treatment reported in the literature of 3 days. [21,22] Limitations of our study include its small sample size, larger studies are warranted to better establish dose equivalency between aboBTX-A and incoBTX-A. IncoBTX-A injections were performed without cost to the patient, and this may have affected patient satisfaction rates.…”
Section: Discussionmentioning
confidence: 99%
“…Although a feared complication, there is an approximate 1 to 6% risk of eyelid ptosis with glabellar neuromodulator injections. 5 Treatment consists first and foremost of patient reassurance. In the majority of cases, the ptosis resolves within 3 weeks as the neuromodulator's effect wears off.…”
Section: Eyelid Ptosismentioning
confidence: 99%